Potential mechanism of primary resistance to icotinib in patients with advanced non–small cell lung cancer harboring uncommon mutant epidermal growth factor receptor: A multi‐center study. Issue 2 (16th January 2020) - Lei, Lei; Wang, Wen‐xian; Zhu, You‐cai; Li, Jin‐luan; Fang, Yong; Wang, Hong; Zhuang, Wu; Zhang, Yin‐bin; Wang, Li‐ping; Fang, Mei‐yu; Xu, Chun‐wei; Wang, Xiao‐jia; et al.
Abstract: The incidence of epidermal growth factor receptor uncommon mutation (EGFRum) is relatively low and patients harboring EGFRum are resistant to the first‐generation tyrosine kinase inhibitors (TKI). However, the mechanism of primary resistance remains unclear. Medical records of 98 patients who had never been treated by TKI and who accepted icotinib treatment were collected and followed. The circulating tumor DNA (ctDNA) were detected and analyzed using the next‐generation sequencing (NGS) platform after progression on icotinib. The potential primary resistance mechanism of icotinib was explored. A total of 21 (21.4%) and 48 (49%) patients developed primary and acquired resistance to icotinib, respectively. The median progression‐free survival (PFS) of primary resistance patients was 1.8 months (0.5‐2.3, 95% CI = 1.50‐2.10). Before treatment, 52.4% (11/21) of patients carried S768I, 23.8% (5/21) L861Q, 14.3% (3/21) G719X and 14.3% (3/21) exon 20‐ins mutations. Approximately 23.8% (5/21) of patients harbored the combined pattern mutations and 76.2% (16/21) of patients harbored the single pattern mutations. The combined pattern with EGFR classical mutation (EGFRcm) had worse PFS than the combined with EGFRum and single pattern ( P  < .05). There were 6 (28.57%) patients with acquired EGFR extracellular domain mutation, 5 (23.81%) with BCL2L11 loss (BIM deletion polymorphism), 3 (14.29%) with MET amplification, 1 (4.76%) with ERBB2 amplification, 1 (4.76%) with MYC amplification, 1 (4.76%) with PTEN mutation, 1 (4.76%) with PIK3CA mutation and 3 (14.29%) with unknown status. EGFR extracellular domain mutation, BCL2L11 loss, PI3K‐AKT‐mTOR signaling pathway (PTEN and PIK3CA mutations), MET amplification, ERBB2 amplification or MYC amplification might contribute to molecular mechanisms of primary resistance to icotinib in patients with advanced non‐small cell lung cancer harboring uncommon mutant epidermal growth factor receptor. Combined targeted therapy or chemotherapy should be considered in this population. Abstract : In a large‐scale multi‐center real‐world study in China, we detected and analyzed potential primary resistance to icotinib in EGFRum patients using the next‐generation sequencing (NGS) platform. EGFR extracellular domain mutation, BCL2L11 loss, PI3K‐AKT‐mTOR signaling pathway (PTEN, PIK3CA mutations), MET amplification, ERBB2 amplification or MYC amplification might contribute to primary resistance of icotinib in EGFRum NSCLC patients.